PRIVATE PENSION SYSTEM - Wong Torres, Zelma (2013)
This article is based on research study entitled “ Implementation of an appropriate internal control for private pensions systems ( AFP ) “ , where it is determined to be studied in depth this system, which has been taken from the Chilean model and it is known that is poised to fail. Therefore, it is necessary to alert members to take a better decision, consider joining the system that suits our prospects and aspirations. It is possible, describe the current situation of the pension system and highlight each of the features, to ensure that workers decide rationally and choose to choose it deems appropriate, also, that the measures taken by the Peruvian Executive Power to serve as a remedy for the problems of the private pension system, among them protect future retirees, because its contributing for its development, poverty reduction will be achieved and provide care in their old age.